Pengaruh Penggunaan Model Pembelajaran Writing in the Here and Now terhadap Kemampuan Mengingat Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam - Pratiwi, Intan; Herni, Zulfiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
Student memory in the History of Islamic Culture subject for class III students at MIS Nurul Hadina is still relatively low, so varied learning models are needed to overcome this problem.“writing in the here and now” is one learning model that teachers can use in the learning process to improve students' memory. Therefore, this research was conducted to determine the effect of learning models“writing in the here and now” in improving students' memory skills in the History of Islamic Culture subject. This research employed quantitative method with a quasi-experimental design as a research type. The research instrument was a questionnaire with a paired sample t-test and an independent sample t-test to test the hypothesis. The research results showed a significant positive relationship between the use of learning models“writing in the here and now” to improve students' memory skills in the history of Islamic culture subject with a 2-tailed significant value of 0.000 < 0.05. The tests (Pre-test and post-test) proved this influence in which students’ memory scores in the experimental class was 7.50 became 10.88 or increased up to 3.33. On the other hand, the control class score was 7.46 became 9.15 or increased up to 1.69. This achievement is surely caused by students’ enthusiasm during the implementation of this learning model.